Daniel Edgar Sickles papers - Sickles, Daniel Edgar, 1819-1914.
Correspondence, speeches, documents, legal and financial records, clippings, printed matter, and other papers. Includes drafts of reports to the U.S. secretary of state while Sickles was serving as U.S. minister to Spain (1869-1873) relating, in part, to the Cuban Insurrection (1868-1878) and the Virginius affair. Other topics include Sickles's service as U.S. representative in the 53rd Congress and as chairman (1886-1912) of the New York (State) Monuments Commission for the Battlefields of Gettysburg and Chattanooga. Correspondents include Sickles's son, George Stanton Sickles; his father, George Garrett Sickles; William McKinley; Theodore Roosevelt; and Elihu Root.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
U.S. Army officer, U.S. representative from New York, and diplomat.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: McKinley, William, -- 1843-1901 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Sickles, George Garrett, -- Correspondence; Sickles, George Stanton, -- Correspondence; New York (State). -- Monuments Commission for the Battlefields of Gettysburg and Chattanooga; United States. -- Congress -- 1893-1895). -- House; Virginius (Steamer); Chattanooga, Battle of, Chattanooga, Tenn., 1863.; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Cuba -- History -- Insurrection, 1868-1878.; Spain -- Foreign relations -- United States; United States -- Foreign relations -- Spain; United States -- History -- Civil War, 1861-1865 -- Monuments; Army officers; Diplomats; Representatives, U.S. Congress -- New York (State)